Penerapan Siklus Plan-Do-Study-Act (PDSA) sebagai Upaya Peningkatan Kepatuhan Perawat dalam Pencegahan Risiko Jatuh Pasien di Rumah Sakit - Lannasari Lannasari; Solehudin Solehudin; Inas Syabanasyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Nurses' compliance in implementing fall risk prevention is a crucial indicator of successful patient safety implementation in hospitals. However, compliance with standard operating procedures for fall risk prevention remains a challenge, necessitating a systematic and sustainable quality improvement strategy, one of which is the Plan–Do–Study–Act (PDSA) cycle. Objective: This study aimed to analyze the effect of implementing the PDSA cycle on nurses' compliance in preventing patient fall risk in hospitals. Methods: This study employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The sample consisted of 20 staff nurses selected using a total sampling technique. Data were collected through an observation sheet assessing nurses' compliance before and after PDSA implementation. Data were analyzed descriptively, followed by normality tests using Shapiro–Wilk, Kolmogorov–Smirnov, and Anderson–Darling, as well as a Paired Samples t-test with a significance level of 5%. Results: The mean compliance score increased from 74.3 ± 7.78 before the intervention to 90.2 ± 5.95 after PDSA implementation. The normality test results indicated that the data were normally distributed (p > 0.05). The Paired Samples t-test showed a significant difference between the pretest and posttest scores (t = -6.83; p = 0.001), with an effect size of 1.53, indicating a very large effect. Conclusion: The implementation of the PDSA cycle was proven effective in improving nurses' compliance in preventing patient fall risk. The application of PDSA is recommended as a continuous quality improvement strategy to support patient safety and enhance the quality of hospital services.